Roman Shakespeare : warriors, wounds, and women - Kahn, Coppélia (Routledge, 1997)
Annotation The first full-length study of Shakespeare's Roman plays offers fresh, detailed readings and identifies new sources which are analyzed from a historical feminist perspective.
Keywords: Shakespeare, William, -- 1564-1616 -- Knowledge.; Shakespeare, William, -- 1564-1616 -- Political and social views.; Shakespeare, William, -- 1564-1616; Feminism and literature -- England -- History -- 17th century.; Masculinity in literature.; Wounds and injuries in literature.; English drama -- Roman influences.; Sex role in literature.; Heroes in literature.; Women in literature.; Rome -- In literature.; Women -- history; Drama -- history; Masculinité dans la littérature.; Lésions et blessures dans la littérature.; Rôle selon le sexe dans la littérature.; Héros dans la littérature.; Femmes dans la littérature.; LITERARY CRITICISM -- Shakespeare.; DRAMA -- Shakespeare.; English drama -- Roman influences; Feminism and literature; Heroes in literature; Literature; Masculinity in literature; Political and social views; Sex role in literature; Women in literature; Wounds and injuries in literature; England; Rome (Empire); 1600-1699; Electronic books.; History